Guanidine N-methylation by BlsL Is Dependent on Acylation of Beta-amine Arginine in the Biosynthesis of Blasticidin S - Wang, Xiankun; Du, Aiqin; Yu, Guiyang; Deng, Zixin; He, Xinyi (Frontiers in Microbiology, 2017)
The peptidyl nucleoside blasticidin S (BS) produced by Streptomyces griseochromogenes was the first non-mercurial fungicide used to prevent rice blast and increasingly used as a selection reagent in transgenic study. An intriguing question around BS final biosynthetic steps is the intermediacy of leucyldemethylblasticidin S (LDBS) as it has not been isolated as a metabolite and its synthetase activity remained to be demonstrated in S. griseochromogenes. In this study, we isolated LDBS in a BS heterologous producer Streptomyces lividans WJ2 upon deletion of blsL, encoding a SAM-dependent guanidine methyltransferase. Purified BlsL efficiently methylate LDBS to LBS at the delta N of beta-arginine, but nearly didn’t methylate intermediate demethylblasticidin S (DBS) to BS. Above experiments demonstrated that LDBS is indeed an intermediate and acylation of beta-amino group of arginine side chain is prerequisite for efficient guanidine N-methylation in addition to being a protected byproduct of the toxic DBS.